Español - Baltuano, Oscar (2020)
The evaluation of a low cost instrument, developed by the authors, for the continuous measurement of the chemical concentrations of NO 2 , SO 2 , NO, H 2 S, CO, PM2.5 and PM10 in urban zones, it has been tested at a point located in the Bellavista district, Callao province, Lima, Peru. The results obtained for an observation time of three months are report. These results are consistent with the expected values for a zone of low vehicle transit and then of low contamination.